5. KAMPANYE POLITIK DAN PENCITRAAN DALAM PILKADA JATENG - Gono, Joyo Nur Suryanto (FORUM, 2008)
Political campaign of Jawa Tengah will be an interesting place for each candidates to political image development. Many issues are expossed by political communication to persuade the specific audience, paid their attention to winning election. Planning and making the strategy of campaign need to the nature of voters, so the messages of campaign achieve them and make change to the voting of candidates.